CAR ALARM SYSTEM WIT H DESIGN DELAY TIME - Ersyat Andi Pribowo; Fivtatianti Hendajani, SKom, MM (Jurnal Sistem Komputer, 2003)
There are many alarms that have been made of people, i n general, the alarm system is switched on or off via a switch that is placed outside the car seat, or car refueling site.Â  Alarms are made in this writing, has a switch which is placed in the lounge car. At the time of turn on the switch, the alarm system is inactive for a while until the owner of the car is outside the car. In an active alarm system, if the car door is opened, the alarm started counting up the numbers that have been determined, the new alarm will provide warning signals such as sirens, hor ns honking, the lights of my life and the engine switched off or not. This warning signal is only live for a while, and then the alarm will be active again. It was a matter for the owner an opportunity to ensure the alarm system so that the warning signal will not be alive.